Neutrophil Activation and Early Features of NET Formation Are Associated With Dengue Virus Infection in Human - Opasawatchai, Anunya; Amornsupawat, Panicha; Jiravejchakul, Natnicha; Chan-in, Wilawan; Spoerk, Nicholas J.; Manopwisedjaroen, Khajohnpong; Singhasivanon, Pratap; Yingtaweesak, Tawatchai; Suraamornkul, Swangjit; Mongkolsapaya, Juthathip; Sakuntabhai, Anavaj; Matangkasombut, Ponpan; et al. (Frontiers in Immunology, 2019)
The involvement of the immune system in the protection and pathology of natural dengue virus (DENV) has been extensively studied. However, despite studies that have referred to activation of neutrophils in DENV infections, the exact roles of neutrophils remain elusive. Here, we explored the phenotypic and functional responses of neutrophils in a cohort of adult dengue patients. Results indicated that during an acute DENV infection, neutrophils up-regulate CD66b expression, and produce a more robust respiratory response as compared with that in convalescent or healthy individuals; this confirmed in vivo neutrophil activation during DENV infection. Spontaneous decondensation of nuclei, an early event of neutrophil extracellular trap (NET) formation, was also markedly increased in cells isolated from DENV-infected patients during the acute phase of the infection. In vitro incubation of NETs with DENV-2 virus significantly decreased DENV infectivity. Interestingly, increased levels of NET components were found in the serum of patients with more severe disease form – dengue hemorrhagic fever (DHF), but not uncomplicated dengue fever , during the acute phase of the infection. Levels of pro-inflammatory cytokines IL-8 and TNF were also increased in DHF patients as compared with those in healthy and DF subjects. This suggested that NETs may play dual roles during DENV infection. The increased ability for NET formation during acute DENV infection appeared to be independent of PAD4-mediated histone H3 hyper-citrullination. Our study suggests that neutrophils are involved in immunological responses to DENV infection.